2018
DOI: 10.15809/irriga.2018v23n1p87
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Do Medidor Ultrassônico De Vazão Em Diferentes Tubos De Policloreto De Vinila

Abstract: DESEMPENHO DO MEDIDOR ULTRASSÔNICO DE VAZÃO EM DIFERENTES TUBOS DE POLICLORETO DE VINILA  BRUNA DALCIN PIMENTA1; ADROALDO DIAS ROBAINA1; MARCIA XAVIER PEITER1; JARDEL HENRIQUE KIRCHNER1; WELLINGTON MEZZOMO1 E ROGÉRIO RICALDE TORRES2 1Departamento de Engenharia Rural, Pós-Graduação em Engenharia Agrícola, Universidade Federal de Santa Maria, Av. Roraima, nº 1000, Bairro Camobi, 97105-900, Santa Maria, RS, Brasil. E-mail: brunadpimenta@gmail.com; diasrobaina@gmail.com; mpeiter@gmail.com; jardelkirchner@hotmail.c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…In comparing two flow rate measurement methods for PVC tubes, Pimenta et al (2018) obtained "Excellent" classification for most of its results with high index of agreement, degree of correlation and performance index values, being similar to the results of the present study.…”
Section: /8supporting
confidence: 87%
See 3 more Smart Citations
“…In comparing two flow rate measurement methods for PVC tubes, Pimenta et al (2018) obtained "Excellent" classification for most of its results with high index of agreement, degree of correlation and performance index values, being similar to the results of the present study.…”
Section: /8supporting
confidence: 87%
“…The results in this study are similar to those of Pimenta et al (2018) in comparing two methods to measure the flow rate. These authors observed that the values demonstrated strong adherence to the regression line, indicated by the high…”
Section: /8supporting
confidence: 85%
See 2 more Smart Citations
“…In the absence of permanent measurements of flow in waterworks, or where accuracy is doubtful, the most commonly used practice is to compare the results that can be obtained from several different portable control meters (these are, as a rule, portable ultrasonic meters) [8][9][10][11][12][13][14][15][16]. We will also test our approach in this manner.…”
Section: Introductionmentioning
confidence: 99%